Study of IR-drop induced jitter in high precision timing ASICs - Peninon Herbaut, David (2024)
The design, testing and manufacturing of application-specific-integrated circuits (ASICs) have become increasingly complex due to large-scale device integration and advancements in technology scaling. Very-large-scale integration (VLSI) has remarkably enhanced electronic circuit performance, impacting profoundly on daily life through various applications such as efficient microprocessors and larger memory chips. Despite these improvements, new challenges have arisen, particularly in designing an efficient power delivery network (PDN) that ensures a stable and evenly distributed power supply across the chip.